The integration of information and communication technologies in the training of physics teachers at the Federal Institutes of the State of Rio Grande do Sul (Research, Society and Development, 2020)
These days, Information and Communication Technologies (ICT) are part of people’s day-to-day in many different sectors, including in the equipment and entertainment industries. In thinking about teacher education in Physics, the literature brings several references that have as their object a more formidable education. The aim is that teachers be better equipped to select, elaborate, and evaluate teaching strategies that are coherent with the demands of today’s society, that are based on their foundational objectives, and that potentialize the use of ICT in the Physics teaching-learning process. This reasoning brings us to analyze the education that Physics Educators receive, as outlined in the respective political pedagogical projects, in the Federal Institutes of Rio Grande do Sul State. The intention is to understand the educational process of these subjects in respect to the development of pedagogical practices by using the new technologies in a critical and creative manner. In order to achieve the research purposes here outlined, a document analysis of the pedagogical projects of the Physics Teaching courses was conducted. Grounded in this analysis, a reflection on the education of these future educators and the potential behind the ICT ensued. The research points to the importance held by public policies and the models of adoption/integration of the ICT, which agree that integration does not happen instantaneously, but actually as a process. For this reason, it is important to broaden the contact and the experience that teachers have with ICT beginning in the process of their initial education. Disciplines such as teaching methodology, classroom management and student teaching present excellent opportunities to contemplate the use of these resources.